Respuesta :

Answer:

[tex]x=\dfrac{-3+5\sqrt{3}i}{2}[/tex] and [tex]x=\dfrac{-3- 5\sqrt{3}i}{2}[/tex].

Step-by-step explanation:

The given equation is

[tex]x^2+3x+21=0[/tex]

To make it complete square add and subtract square of half of coefficient of x.

[tex]x^2+3x+21+(\dfrac{3}{2})^2-(\dfrac{3}{2})^2=0[/tex]

[tex]x^2+3x+(\dfrac{3}{2})^2+21-\dfrac{9}{4}=0[/tex]

[tex](x+\dfrac{3}{2})^2+\dfrac{75}{4}=0[/tex]

[tex](x+\dfrac{3}{2})^2=-\dfrac{75}{4}[/tex]

Taking square root on both sides.

[tex]x+\dfrac{3}{2}=\pm\sqrt{-\dfrac{75}{4}}[/tex]

[tex]x+\dfrac{3}{2}=\pm\dfrac{5\sqrt{3}i}{2}}[/tex]

[tex]x+\dfrac{3}{2}=pm \dfrac{5\sqrt{3}i}{2}}[/tex]

[tex]x=-\dfrac{3}{2}pm \dfrac{5\sqrt{3}i}{2}}[/tex]

[tex]x=\dfrac{-3\pm 5\sqrt{3}i}{2}[/tex]

Therefore, the roots of the given equation are [tex]x=\dfrac{-3+5\sqrt{3}i}{2}[/tex] and [tex]x=\dfrac{-3- 5\sqrt{3}i}{2}[/tex].